New insights on the origin of Barra volcanic ridge system, offshore Ireland: A long-distance influence of the Iceland mantle plume. (June 2023) - Tomar, Gaurav; Roy, Srikumar; Bean, Christopher J.; Singh, Satish C.; O'Reilly, Brian; Schofield, Nick
Abstract: The Iceland Plume has significantly impacted the North Atlantic region. Igneous edifices and large seamounts in the Rockall region were linked to Iceland plume pulsations during the Late Cretaceous to Mid-Eocene. In the south of the Rockall Basin a chain of northwest-southeast trending volcanic ridges known as the Barra Volcanic Ridge System (BVRS) have been identified on seismic and magnetic datasets. However, the timing, morphology, extent, and emplacement mechanism of the BVRS are not well understood. To investigate the volcanic ridge system, we analyze a 360-km-long pre-stack time migrated seismic section along the margin, which covers the southern extent of BVRS. The high velocity (4.5–4.8 km/s) obtained by using first arrival travel time tomography of downward continued data set, high magnetic anomaly and the typical morphology of the ridges suggest that they could be volcanoes of basaltic compositions. The integration of gravity and seismic data constrain the crustal structure and thickness, which indicates that the crust could be as thin as 4 km beneath the BVRS, requiring a maximum stretching factor >6. Folded compressional structures and lava flows within the Early Paleocene to Mid-Eocene sediments draping the volcanic ridges, suggest that these volcanic intrusions possibly have occurred post Early Paleocene age, which is approximately the same time-period when Iceland mantle plume arrived in the Rockall region. These results suggest that the BVRS developed because of pre-existing lithospheric configuration in the Rockall Basin and could be one of the southernmost volcanic provinces of the North Atlantic Igneous Province (NAIP). Highlights: We present the crustal to upper mantle model of the south Rockall Basin by using pre-stack time migrated seismic section. Four volcanic ridges are delineated as part of the Barra Volcanic Ridges System (BVRS) in the south of the Rockall Basin. The results suggest that the development of the volcanic ridges in the basin might have an influence of the Iceland Mantle Plume. A highly stretched thin crust is present beneath the BVRS. We observe a stretching factor β > 3 across the full extent of the NE-SW section and β > 6 beneath the BVRS.